(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Developing writing skills is one of the most important aspects of learning a foreign language. It is crucial for learners to be able to effectively communicate their ideas and thoughts in writing, as writing is a key tool for conveying information and expressing oneself. In this article, we will dispute how to be a good foreign language writer, and outline seven ways we can enhance our foreign language writing skills.